(untitled) (Journal of Management and Social Sciences, 2018)
Abstract The Nigerian economy has just technically exited recession. This harsh economic condition is no doubt of great concern to the government and people of the country in view of its attendant pains. Economic and financial experts and professionals are expected to find solution to this national challenge. This paper however argues that, in addition to seeking economic solution to this problem, the nation’s public service in its position as the main machinery of government for the formulation and implementation of public policies should be recognised as a critical factor in exiting the country out of recession. This can be done by continuous training and re-training of public servants in order to increase their competence, morale and productivity towards speedy recovery of the country’s economy. The paper adopted the qualitative method of analysis using mainly secondary source of data. Keywords Training, development, economic recession, economic recovery, performance improvement, training needs